Atypical cerebral MRI imaging findings in a patient with isolated neurosarcoidosis - Mohamed Reda Cherkaoui Jaouad; Amal Miqdadi; Mohamed Mahi; Sophia Berrada (Radiology Case Reports, 2024)
Sarcoidosis is a rare, chronic, granulomatous disease of unknown etiology and primarily effects the lymphatic and respiratory systems. The central nervous system (CNS) is unusually implicated in sarcoidosis patients. We describe a rare magnetic resonance imaging (MRI) findings in a case of isolated neurosarcoidosis. The evaluation of suspect patients requires radiological imaging studies, especially MRIs. The diagnosis of neurosarcoidosis is clinically challenging, MRI studies are effective in detecting CNS inflammation but lack specificity.